ANALISIS VICTIMOLOGI TERHADAP KORBAN TINDAK PIDANA PENIPUAN ONLINE SHOP DI KABUPATEN BULELENG - Komang Sri Wahyun; hartono, made sugi; Dewa Bagus Sanjaya (Jurnal Ilmu Hukum Sui Generis, 2025)
This research aims to determine the factors that cause someone to become a victim of online shop fraud and the steps and efforts to protect victims of online shop fraud in Buleleng Regency. The type of research that will be used in this research is empirical legal research. In examining this case, the research uses descriptive characteristics. The data used in this research are Primary Data and Secondary Data consisting of Primary Legal Material, Secondary Legal Material and Tertiary Legal Material. The conclusions from this research are 1) the factors that cause someone to become a victim of Online Shop fraud in Buleleng Regency, so it can be concluded that the factors that cause someone to become a victim of Online Shop fraud in Buleleng Regency are internal factors consisting of very high prices. cheap, because of the ease of transactions on Social Media and the lack of public insight and knowledge regarding the latest modes of fraud as well as external factors which include economic factors, education factors, cultural factors and environmental factors. 2) The steps and efforts to protect victims of Online Shop fraud in Buleleng Regency which have been carried out by the Buleleng Police Unit and the Buleleng Regency Communication, Informatics, Coding and Statistics Service are preventive legal protection consisting of providing Digital Literacy education and socialization and repression which consists of from settlement through legal channels by the Buleleng Police Unit. Furthermore, the Buleleng Regency Communication, Information, Coding and Statistics Service has also provided reporting for cellphone numbers and account numbers that are indicated to be fraudulent to help other people trace the history of these numbers.